ChatGPT as Facilitator or Hindrance in Academic Writing: A Systematic Review and Practical Recommendations - Annisa Permata Islami (Journal of Educational Sciences, 2026)
In today’s world, ChatGPT as a large language model (LLM) has brought a significant impact in education, especially in academic writing skills for EFL (English as Foreign Language) learners. This study investigates the benefits and limitations of using ChatGPT in the context of EFL learners as well as provide recommendations for the stakeholders. A total of 22 scientific articles were systematically analyzed using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines as the basis for systematic review and meta-analysis. The results presented four main benefits of using ChatGPT in academic writing, namely: (1) improved language and cognitive competence; (2) provision of personalized feedback; (3) increased efficiency of the writing process; and (4) enhanced confidence and self-efficacy. On the other hand, a number of limitations were also found, including: (1) risks to academic integrity; (2) low quality and reliability of information; (3) over-reliance on instant feedback; and (4) social, cultural, and technical challenges. In response to these findings, this study presents practical recommendations for students and teachers in the form of lesson designs that integrate ChatGPT with traditional teaching methods. Moreover, this paper also includes recommendations for decision-makers to maximize the potential of this technology in language education.